a2-6a-27=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -27 and whose sum is -6.

-9,3

Write the factored form using these integers.

(a-9)(a+3)=0

(a-9)(a+3)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

a-9=0

a+3=0

Set the first factor equal to 0.

a-9=0

Add 9 to both sides of the equation.

a=9

a=9

Set the next factor equal to 0.

a+3=0

Subtract 3 from both sides of the equation.

a=-3

a=-3

The final solution is all the values that make (a-9)(a+3)=0 true.

a=9,-3

Solve for a a^2-6a-27=0